Study the effect of Thymus vulgaris on the weight of Liver and Kidneys in Albino male rats (Journal of the College of Basic Education, 2022)
The increase in the outbreak of the use of thyme in Iraq and in neighboring countries, especially in recent times of medical and nutritional point of view and may be caused by excessive use of thyme from side damage and which may reach the critical stage, Therefore, this study aim to assess the effect (500 , 750 ,1000 ) mg / kg of body weight of thyme extraction given to rats by injection and feeding by grinding dried thyme leaves adding to pellet ( 50 ,100 , 150 ) g / kg of pellet in the difference duration ( 10 , 20 , 30 ) days for injection and feeding per 2 times in week on the weight of each of the liver and kidneys in male rats, The statistical analysis shows that thyme cause significant decrease (P≤0.05) in weight of liver and kidney in rats that treated with thyme extraction by 1000 mg /kg of body weight and 150 g / kg of pellet in duration 10 days , in 20 days thyme cause high significant decrease (P≤0.01) in weight of liver and kidney in rats that treated with thyme by 750 - 1000 mg /kg of body weight and 100 - 150 g / kg of pellet and in 30 days thyme cause very high significant decrease (P≤0.001) in weight of liver and kidney in rats that treated with thyme extraction by 500 - 750 - 1000 mg /kg of body weight comparing with the negative and positive controls and 50 - 100 - 150 g /kg of pellet comparing with the negative control for feeding